BASIC APPROACHES TO IMPROVING THE ORGANIZATION COST MANAGEMENT SYSTEM - Panfilova E. E., Petrakova P. K. (Science and education: future development, 2019)
The article discusses the issues of effective cost management at the enterprise. Attention is paid to organizational issues of introducing management accounting system at the enterprise. The features of cost management at a catering enterprise are clarified, the stages of the accounting process are highlighted in the cost centers of the organization.
Keywords: контроллинг; аудит; предприятие; затраты; центр ответственности; costs; enterprise; controlling; audit; responsibility center